Short Inscription on a pillar in the Mahamandapa - Temples of India Project Team (Jio Institute, 2024)
On one of the pillars in the mahamandapa (pillared hall) of the Bisaldeo Temple is a short inscription which mentions the name of ‘Jogi Achpantadhaja’ or ‘Yogi Achintyadhvaja'.